Pengaruh Pengalaman Pembelajaran Praktik Dan Kemampuan Berpikir Kritis Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Instalasi Penerangan Listrik Kelas XII SMK Negeri 7 Surabaya - Mukti Hidayat Pradany; Rina Harimurti (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
Electrical Power Installation Engineering at State Vocational High School 7 Surabaya giving lessons on electric lighting installation. In the process of teaching and learning, practical learning provides real provision regarding electrical lighting installation engineering material. Practical learning must be in accordance with the needs of human resources in the world of business and industry, this discrepancy will result in incompetent human resources in the industrial world. Based on the results of observations made at State Vocational High School 7 Surabaya, it was found that in the learning process students still did not have good critical thinking skills in completing school assignments, both theoretical and practical assignments. Therefore, the existence of this research is an effort to determine the effect of practical learning experiences and critical thinking skills on student learning outcomes. This research involved class XII students majoring in Electrical Power Installation Engineering (TITL) at State Vocational High School 7 Surabaya. The research method used is comparative causal research or what is commonly called the ex-post facto method. This research was conducted at State Vocational High School 7 Surabaya, Department of Electrical Installation Engineering with a population of students at State Vocational High School 7 Surabaya Class XII TITL Electrical Installation Engineering Expertise Program and the sampling technique used was Purposive Sampling. The data collection was obtained through a questionnaire to determine the level of practical learning experience, a description test to determine the level of critical thinking skills, and a multiple choice test to determine learning outcomes of knowledge competencies and observation to determine learning outcomes of skills competencies. Practical learning experience affects the learning outcomes of knowledge competencies based on partial tests with a t count (2.625) greater than t table (1.993) with a significance value of 0.011 <0.05. The practical learning experience has an effect on the learning outcomes of skill competencies based on the partial test with a t count (3.185) greater than t table (1.993) with a significance value of 0.002 <0.05. The ability to think critically affects the learning outcomes of knowledge competence based on the partial test with a t count (3.138) greater than t table (1.993) with a significance value of 0.002 <0.05. The ability to think critically affects the learning outcomes of skill competencies based on the partial test with a t count (2.716) greater than t table (1.993) with a significance value of 0.008 <0.05. Practical learning experience and critical thinking skills affect learning outcomes of knowledge competency based on multiple linear regression analysis with a calculated F value (4.979) greater than F table (3.13) with a significance value of 0.009 <0.05. Practical learning experience and critical thinking skills affect learning outcomes of skill competencies based on multiple linear regression analysis with a calculated F value (5.100) greater than F table (3.13) with a significance value of 0.009 <0.05.